The analysis of Colombian Foreign Policy: a state of the art - González Parias, Carlos Hernán (2020)
the analysis of Colombian foreign policy produced in the last two decades (2000-2019), therefore, it is a state of art. There were several objectives that guided the realization of the same, including the following: determine the current trends, possible research gaps and the level of activity of this line of research, and identify the methodologies used as well as the theoretical orientations of these analyzes. It is concluded that Colombian foreign policy studies are a line of dynamic and active research, which has passed the stage of mere description and generalizations, which has given way to broader theoretical-methodological orientations for the analysis of specific situations and a greater depth in the explanatory factors.